Evaluation of Cadmium Contaminations in Soil and Plants, and Potential Ecological Risk at a Tertiary Institution Campus, Malete, Kwara State, Nigeria - P. O. Ben-Uwabor; S. O. Olarinoye (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to evaluate the cadmium contaminations in soil and plants, and potential ecological risk at a tertiary institution campus, Malete, Kwara State, Nigeria using appropriate standard procedures. Data obtained indicates highest cadmium concentration in plants at the library (0.282±0.03 mg/kg), while the highest soil concentrations were observed at the School Park (0.316±0.04 mg/kg). The cadmium Contamination Factor (CF) and Bioaccumulation Coefficient (BAC) assessed the degree of pollution on the campus and the amount of Cd uptake by the plants, with moderate contamination across most sites, recording the Administrative Building area to display a notably higher Contamination Factor of 2 and cadmium Potential Ecological Risk index of 60, indicating a moderate ecological risk with Azadirachta indica  and Delonix regia been hyperaccumulators of cadmium.These findings showed the need for cadmium monitoring and targeted friendly environmental management, particularly in areas with elevated cadmium levels. The study concludes that while cadmium contamination is a campus-wide issue, specific locations, such as the Library and Administrative Building, require urgent attention to mitigate potential environmental and public health risk.